ANALISIS HIGHER ORDER THINKING SKILLS (HOTS) SISWA SMP N 1 SALO DALAM MENYELESAIKAN SOAL UJIAN NASIONAL IPA FISIKA TINGKAT SMP/MTs - Uulia 'Iffa; Fakhruddin '; Yennita ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This research aims to determine the national exam HOTS science physics and HOTS students of SMP N 1 Salo in completing the national exam science physics. This type of research is descriptive research, content analysis or document type. The research subjects are students of class IX SMP N 1 Salo, namely class IXA - IXF amount of 139 students. The data in this study a matter of HOTS percentage in the national exam in 2014, 2015 and 2016, subsequently measured absorption students work on the problems that have category HOTS in the national examinations in 2016 were analyzed descriptively. Based on data analysis were categorized HOTS matter in the national exam in 2016, 2015 and 2014 respectively 8.7%, 11.7%, and 0%. Absorptive capacity of students in work on the problems that have category HOTS on the national exam in 2016 with a percentage of 20.1%. It can be concluded that the category HOTS matter on the national exam science physics is still very low and HOTS students in completing the national exam science physics in 2016 is still low.Key Words: High Order Thinking Skills (HOTS), National Examination, Science Physics